Effects of biochar amendment on the soil silicon cycle in a soil-rice ecosystem. (May 2019) - Wang, Yaofeng; Xiao, Xin; Zhang, Kun; Chen, Baoliang
Abstract: For the soil-plant ecosystem, knowledge about the effects of biochars on the soil silicon (Si) cycle is still tenuous. In this study, the effect of biochars on the yield, Si uptake and Si distribution within different tissues of rice plants and the soil Si cycles in a soil-plant system were investigated. Si-rich (RH300-700) and Si-deficient (WB300-700) biochars prepared from rice husk and wood sawdust were applied to high-Si soil (HSS) and low-Si soil (LSS). Biochar addition increased the yield of grain and straw and had no effect on the yield of root, and the increase in the yield with Si-rich biochars was obvious; this effect had a high response to LSS. Si-rich biochars increased the plant Si content of grain and root and had no effect on straw. RH300 amendment increased the Si concentration in grains, compared to RH500 and RH700. The addition of Si-deficient biochar to HSS had little effect on the Si content, while Si-deficient biochar-amended LSS had a great impact on the reduced Si content in rice straw and root, and WB700 decreased the Si concentration in grains, compared to WB300 and WB500. Finally, the Si-rich biochars increased the total Si uptake within rice, while Si-deficient biochars decreased the total Si uptake in LSS. According to the FTIR and SEM-EDX spectra of biochars before and after rice harvest, a new band of SiOSi at 471 cm −1 was found after aged WB700, and the minerals of iron and Si were found on the surface of aged WB700; biochars can fix the dissolved Si on its surface as a temporary store to prevent Si loss. Therefore, biochars can be considered reservoirs of soil Si, which is a slow release source of available Si, to impact the speed of biogeochemical cycling of soil Si in agricultural paddy soil. Graphical abstract: Image 1 Highlights: Si-rich biochar additions increased the Si content in rice grain and roots. Si-rich biochar amendments promoted the total Si uptake by rice plants. Si-deficient biochar decreased the total Si uptake of rice in low-silicon soil. Biochars are adsorbents that can fix the dissolved Si on its surface as a reservoir. Si biocycling in soil–plant systems can be readily affected by biochar aging. Abstract : Si-rich biochar additions increased the Si content in rice grain and roots, and promoted the total Si uptake by rice plants, but Si-deficient biochar decreased the total Si uptake of rice in low-silicon soil.